A Comparative Study of the Antibacterial Effect of Three Ethnomedical Plants (Ocimum gratissimum, Vernonia amygdalina and Cymbopogon citratus) on Certain Clinical Isolates - Obhioze Augustine Akpoka *; Maureen U. Okwu; Odaro Stanley Imade; Spencer C. O. Nwangwu; Erifeta Georgina Omonegho; Christabel Uti (Herbal Medicines Journal, 2019)
Background and Aim: Ethnomedicinal plants are used by indigenous populations all over the world as remedies for various maladies. The present study aimed at evaluating the antibacterial susceptibility of the leaves of Cymbopogon citrates, Vernonia amygdalina and Ocimum gratissimum against Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and methicillin-resistant Staphylococcus aureus.